The Effect Of Company Size And Capital Structure On Company Value (Study On Property And Real Estate Companies Listed On The Indonesian Stock Exchange) - Nastiti Rizky Shiyammurti; Yanti Ramadanti (Jurnal Scientia, 2024)
The purpose of this study was to examine and determine the effect of firm size and capital structure partially and simultaneously on firm value. This study uses property and real estate companies listed on the Indonesia Stock Exchange during the 2016-2022 period as the population. The sampling technique used is purposive sampling method where the sample is taken based on certain criteria according to the will of the researcher, so that based on these retrieval criteria a sample of 140 companies is obtained. This study uses secondary data and the data analysis method is carried out by multiple linear regression tests with the help of SPSS version 25 software as a data processing programme. In this study, the ratio used as an indicator to measure the dependent variable of firm value is PBV (Price to Book Value). The results of this study indicate that partially firm size and capital structure have a significant and negative effect on firm value. While simultaneously firm size and capital structure have a significant and positive effect on firm value.